2017
DOI: 10.1039/c7nr02843a
|View full text |Cite
|
Sign up to set email alerts
|

An organometallic route to chiroptically active ZnO nanocrystals

Abstract: The unique optical properties of zinc oxide nanocrystals (ZnO NCs) are strongly dependent on both the properties and the composition of the inorganic core-organic ligand interface. Developing a novel organometallic self-supporting approach, we report on the synthesis and characterization of ZnO nanocrystals coated by chiral monoanionic aminoalcoholate ligands. The resulting ZnO NCs are both chiroptically active and possess size dependent optical properties. The size and in consequence the emission color of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 39 publications
0
25
0
Order By: Relevance
“…Different ligand precursors lead to NPs with a variety of properties and applications. [176][177][178][179][180][181][182][183] TEM micrograph reproduced with permission from the RSC. 177 the amount of ligand is helpful in forming composite materials, where excess ligand would affect the material properties, e.g.…”
Section: Ic Synthesis Of Zno Nps With Strongly Bound Anionic Ligandsmentioning
confidence: 99%
“…Different ligand precursors lead to NPs with a variety of properties and applications. [176][177][178][179][180][181][182][183] TEM micrograph reproduced with permission from the RSC. 177 the amount of ligand is helpful in forming composite materials, where excess ligand would affect the material properties, e.g.…”
Section: Ic Synthesis Of Zno Nps With Strongly Bound Anionic Ligandsmentioning
confidence: 99%
“…Moreover, we have also emphasized the essential role of the coordination state of the oxygenated organoaluminum and organozinc compounds, as well as the geometric requirements of an O 2 molecule approaching the metal centre . Apart from the fundamental aspects, these systematic studies have advanced rational design of metal alkyl/air systems as radical initiators for organic reactions, stoichiometric and catalytic asymmetric epoxidation of enones and pave the way to well‐defined metal alkoxides (not accessible through the classical alcoholysis path) as potential initiators of cyclic esters polymerization as well as to a new approach for the preparation of semiconductor zinc oxide quantum dots based on organozinc/air systems …”
Section: Introductionmentioning
confidence: 96%
“…[33,34] Apart from the fundamental aspects, these systematic studies have advanced rational designo fm etal alkyl/airs ystemsa sr adicali nitiators for organic reactions, [35][36][37] stoichiometric [38,39] and catalytic asymmetric epoxidation of enones [11,14,40] and pave the way to welldefined metal alkoxides (not accessible through the classical alcoholysis path) as potentiali nitiators of cyclic esters polymerization [25,41] as well as to an ew approach for the preparation of semiconductor zinc oxide quantum dots based on organozinc/ air systems. [42][43][44][45][46] Notably,t he oxygenationc hemistry of magnesium alkyls has remained anu ndeveloped area of research due to difficulties to control the respective reactions ystemsr esulting from the exceptionali nstability of MgOOR species. As early as the beginningo ft he XX th centuryB odroux [47] and Bouveault [48] independently observed that oxygenationo fR MgX compounds afforded the corresponding ROH alcohols after the standard workup procedure.…”
Section: Introductionmentioning
confidence: 99%
“…[18] The resulting water-soluble ZnO NCs exhibited unprecedentedu ltralong-lived electron-hole separation (up to 2.2 ms) [18a] and, by taking advantage of the exceptional properties of ZnO NCs modifiedw ith ao ligoethylene glycol carboxylate shell, we created an anohybrid system for H 2 evolution under visible-light irradiation. [21] Following the statement of Cohen and co-workers: [22] "efforts are now mounting to ensure the development and application of safe-by-design engineered nanomaterials so as to avoid adverse environmental and humanh ealth impacts" and advancing the OSSOM method, herein we report on the synthesis of quantum-sized ZnO NCs coated by ad enselyp acked 2-(2-methoxyethoxy)acetate ligand shell as am odel system for in vitro cytotoxicity studies by cell metabolic activity assay (MTT) in normal( MRC-5) and cancer( A549) human lung cell lines. reported another variant of the organometallic approach for ZnO NC synthesis through the hydrolysis of R 2 Zn supported by substoichiometric quantities of zinc carboxylates Zn(O 2 CR') 2 or zinc phoshinatesZ n(O 2 PR' 2 ) 2 and their utility as ac omponent of ZnO/Cu nanocatalysts or antimicrobial polymer surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting ZnO NCs have a unique nanocrystal/ligand interface, as documented by their processability at water/air interfaces, and effective functionalization by the CuAAC reaction with retention of their PL . Moreover, the OSSOM method paves the way to the efficient preparation of chiroptically active ZnO NCs …”
Section: Introductionmentioning
confidence: 99%